Irish population prospects considered from the viewpoint of reproduction rates - Geary, R. C. (Statistical and Social Inquiry Society of Ireland, 1941)
Estimates of future population render explicit the assumption with regard to population statistics, which is implicit in the use of most current statistics, that the tendencies indicated are applicable now and in the near or remote future, though they may actually relate to some time back. My previous estimates have been criticised because they related to the Twenty-Six Counties. The present series also relate to this area, principally because the exact data required for the Six Counties are not available. In order to justify the assumptions on which two of the three series of estimates are based, it will be necessary to consider the recent trend in births, deaths and migration.
Read on Friday, 28th March, 1941
Keywords: Population forecasts; Reproductive rates; 314.15